Extraction technology, component analysis, and in vitro antioxidant and antibacterial activities of total flavonoids and fatty acids from Tribulus terrestris L. fruits. (10th January 2019) - Tian, Chunlian; Zhang, Zehui; Wang, Hong; Guo, Yuru; Zhao, Jihang; Liu, Mingchun
Abstract: The current study focused on the extraction technology, components analysis, in vitro antioxidant and antibacterial activities of total flavonoids and fatty acids from Tribulus terrestris L. fruits. The extraction process of total flavonoids and fatty acids was optimized by the response surface method, and the compositions were identified from the two extracts by HPLC–DAD–ESI–MS − and GC–MS, respectively. In addition, the antioxidant and antibacterial activities were evaluated by assay of ABTS, DPPH radical scavenging activity, ferric reducing antioxidant power and minimal inhibitory concentration. The yields of total flavonoids and fatty acids were 0.46 and 9.76% under the optimized conditions. Moreover, nine and eight compositions were identified from the two extracts based on the related references, respectively. In addition, total flavonoids and fatty acids extracts both exhibited certain antioxidant and antibacterial activities. The present findings suggest that total flavonoids extracted from T. terrestris L. fruits comprised a more interesting candidate than fatty acids for the research and development of natural and healthy antioxidants and antibacterial agents for the pharmaceutical and food industries.